PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENDEKATAN CRT BERBANTUAN MODEL STAD PADA MATERI GARIS DAN SUDUT - Mahmudi; Ranila, Rahayu; Setyadi, Danang (EMTEKA: Jurnal Pendidikan Matematika, 2024)
EEducation is a planned and conscious process aimed at guiding students to optimally develop their physical and spiritual potentials. In this context, mathematics education plays a crucial role in shaping students' critical and creative thinking abilities. However, many students struggle with and dislike mathematics, as observed at SMP Negeri 2 Salatiga. This study aims to improve students' mathematics learning outcomes by applying the Culturally Responsive Teaching (CRT) approach supported by the Student Teams Achievement Divisions (STAD) cooperative learning model on the topic of lines and angles. This Classroom Action Research (CAR) utilized the Kemmis and Taggart model, consisting of two action cycles. Data were collected through observation, tests, and documentation, and analyzed descriptively. The results showed a significant increase in the average mathematics scores from 55.85 in the pre-cycle to 70.42 in the first cycle, and 80.78 in the second cycle. Student activities also improved from "poor" in the first cycle to "good" in the second cycle. The application of CRT with the STAD cooperative learning model effectively enhanced students' understanding and mathematics learning outcomes. This approach integrates local culture into the learning process, making the material more relevant and easier for students to comprehend. This research provides valuable insights into the development of creative and innovative teaching methods to improve the quality of mathematics education in schools